2002
DOI: 10.1046/j.1083-4389.2002.00069.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Helicobacter pylori‐Induced Cyclooxygenase‐2 on Gastric Epithelial Cell Kinetics: Implication for Gastric Carcinogenesis

Abstract: The expression of COX-2 is associated with disruption in gastric epithelial kinetics and hence may play a role in gastric carcinogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 45 publications
1
21
2
Order By: Relevance
“…Up-regulation of COX-2 plays a central role in the inflammatory changes and tissue damages associated with the chronic H. pylori infection, and is also involved in the gastric tumorigenesis (4,5). The expression of COX-2 protein is significantly higher in patients with gastric cancer than those with nonulcer dyspepsia (6). Therefore, COX-2 expression is assumed to play a key role in H. pylori-associated gastric cancer in addition to the propagation of gastric inflammation (7).…”
Section: Helicobacter Pylori-induced Invasion and Angiogenesis Of Gasmentioning
confidence: 99%
“…Up-regulation of COX-2 plays a central role in the inflammatory changes and tissue damages associated with the chronic H. pylori infection, and is also involved in the gastric tumorigenesis (4,5). The expression of COX-2 protein is significantly higher in patients with gastric cancer than those with nonulcer dyspepsia (6). Therefore, COX-2 expression is assumed to play a key role in H. pylori-associated gastric cancer in addition to the propagation of gastric inflammation (7).…”
Section: Helicobacter Pylori-induced Invasion and Angiogenesis Of Gasmentioning
confidence: 99%
“…H pylori infection could also induce gastric mucosal cell proliferation by COX-2 expression. COX-2 gene expression was one of the related factors mediating the progress from gastritis with H pylori infection to pre-carcinoma lesions even gastric carcinoma [16,17] . Based on this study, treatment of H pylori infection and special COX-2 inhibitor could be useful for the prevention of gastric carcinoma [18] .…”
Section: Yu Lz Et Al Expression Of Cox-2 Proteins In Gastric Mucosalmentioning
confidence: 99%
“…Cyclooxygenase is a key enzyme that catalyses the conversion of prostaglandins and other eicosanoids from arachidonic acid. COX-2 is induced during pathologic conditions and is often overexpressed in premalignant lesions and malignant tumors [3,6,24,43,44]. This enzyme is linked to carcinogenesis, maintenance of progressive tumor growth, and facilitation of metastatic spread [4,41].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies indicate that COX-2, an enzyme involved in the metabolic conversion of arachidonic acid to prostaglandins, plays an important role in tumor growth and spread of established tumors by affecting mitogenesis, cellular adhesion, immune surveillance, apoptosis, and angiogenesis [6,21,24,34,44,41,46]. Several studies have shown that COX-2 expression is elevated in human colorectal neoplasia as compared to normal mucosa, thus making COX-2 a potential target for chemoprevention [7,15,42].…”
Section: Introductionmentioning
confidence: 99%